DESIGN AND FABRICATION OF A MANUAL CENTRIFUGAL CASTING DEVICE PROTOTYPE FOR POST COVID-19 RECOVERY GROWTH OF THE TRADITIONAL GOLD JEWELLERY INDUSTRY IN GHANA - Fening, P. A.; Asomaning, K. A.; Isaac Agyei; Adu Boachie, C. (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Innovation in equipment and technology development has been identified as a powerful trigger for SMEs resilience and recovery in the context of the Covid-19 pandemic crisis. This paper presents the design, fabrication and operationalization of a simple but effective centrifugal casting device prototype, for the traditional gold jewellery industry in Ghana. The design process commenced by the conceptual design phase; detailed design phase followed by the embodiment design stage. The device was constructed using local materials. The device is easy to manufacture, maintain and relatively cheap. It can therefore be easily replicated or fabricated by ‘’wayside’’ welders. It is also easily transportable and can be used for teaching and demonstration purposes for students of tertiary institutions. The merit of this project is its innovative concept and constitutes a fundamental and important contribution to the research and development of new pioneering centrifugal casting machine for the local gold jewellery industry in Ghana.